Evolution of mammalian scales and immunity within pangolin genomes and database development / Tan Tze King - Tan, Tze King (2016)
Pangolins (Order, Pholidota) are unique mammals that are edentulous, have poor vision, an acute olfaction system and they possess scales that cover most of their body, Among eight known pangolin species, the Malayan (Manis javanica) and Chinese pangolins (M. pentadactyla) are critically endangered species. In this study, I performed the first comparative genome analysis for the Malayan and Chinese pangolins to investigate pangolin biology and evolution. Strikingly, I found that interferon-epsilon (IFNE), which is exclusively expressed in epithelial cells and important in skin and mucosal immunity, is pseudogenised in all Asian and African pangolin species examined, perhaps impacting resistance to infection. Gene family expansion/contraction analysis clearly showed that Olfactory Receptor (OR) gene families are significantly expanded in pangolins, reflecting their well-developed olfaction system. The significantly contracted IFN gene family was observed, probably reflects poor immunity in pangolins. Interestingly, I also found the pseudogenization of genes responsible for tooth development such as enamelin (ENAM), ameloblastin (AMBN), and amelogenin (AMELX), suggesting that the presumabed loss of function of these genes might be linked to the edentulous characteristics of pangolins. Furthermore, I have identified mutations that cause the loss of Guanylate cyclase activator 1C (GUCA1C) and intermediate filament-like protein (BFSP2) gene functions, potentially affect pangolin vision acuity. In general, my findings reflect the unique traits of pangolins. I hypothesize that the reduced IFN-mediated immunity from the loss of IFNE and the contraction of interferon gene family in pangolins imposed strong selective pressure on immunity-related genes. Identification of positively-selected genes that involving in a wide range of immunity-related pathways including hematopoietic cell lineage, cytosolic DNA-sensing pathway, complement and coagulation cascades, cytokine-cytokine receptor interaction, and the phagosome pathway. This positive selection analysis also provided substantial evidence of pangolin specialized adaptations associated with the energy storage and metabolism, muscular and nervous systems, and scale/hair development. To facilitate research in pangolins, I have developed a Pangolin Genome Database (PGD), aiming to be a future pangolin genome hub for hosting pangolin genomic and transcriptomic data and annotations, and supported by useful analysis tools for the research communities. Currently, the PGD provides the reference pangolin genome and transcriptome sequences, gene and functional information, expressed transcripts, pseudogenes, genomic variations, organ-specific expression data and other useful annotations. Therefore, it will be an invaluable platform for researchers, who are interested in pangolin and mammalian research in future. This study provides insights into mammalian adaptation and functional diversification, new research tools and questions, and perhaps a new natural IFNE-deficient animal model for studying mammalian immunity in future. Lastly, I propose a potential relationship between scales development and IFNE pseudogenization. The development of pangolin scales could hypothetically be a counter mechanism for an inherently poor immune response and provide physical protection against injuries or stress and reduce pangolinï¿½s vulnerability to infection.